(untitled) (XXI Century. Spanish Literature and Culture, 2008)
In recent years, the story had been considered a suitable genre for the remembrance of the recent past and among the diverse tendencies that have prevailed in the past two decades we find a memorial realism cultivated by writers of distinct generations and backgrounds. The focus of the present work are the various stories of the volume Capital de la gloria by Juan Eduardo Zúñiga, that approaches the subject of the Spanish Civil War at different times, while always having Madrid and its surrounding areas as the setting and presenting the action from the perspective of the defeated. The aesthetics of metamorphosis appear in these stories and is one of the characteristics that define the narrative of the author. The theories of Mikhail Bakhtin allow a critical approximation of these fictions through the aesthetics of the idyll, the values of the home land and the family.